The Validity of Artificial Intelligence Evidence in the Judicial System: A Juridical Analysis - Dewi. M, Nur Sari; Muslem, Muslem (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
The advancement of Artificial Intelligence (AI) technology ideally strengthens the criminal justice system by enhancing effectiveness, efficiency, and accuracy in the process of evidence examination. AI can process large volumes of data and assist law enforcement in systematically identifying crime patterns. However, in reality, Indonesia’s legal system still adheres to conventional evidentiary paradigms as stipulated in the Criminal Procedure Code (KUHAP) and the Electronic Information and Transactions Law (UU ITE), which have not yet explicitly recognized AI-based evidence. This condition raises issues of validity, accountability, and legal fairness, particularly because AI-generated outputs lack legal subjects that can be held responsible and are vulnerable to algorithmic bias. This study aims to analyze the validity of AI-based evidence within Indonesia’s criminal justice system through a normative legal study employing statutory, conceptual, and comparative approaches. The findings reveal a significant legal vacuum in the regulation of AI evidence, resulting in uncertainty and potential human rights violations. Therefore, legal reform is necessary through amendments to the UU ITE, the formulation of technical guidelines via Supreme Court Regulations (PERMA), and the strengthening of law enforcement capacity to ensure that AI utilization aligns with the principles of justice, transparency, and due process of law in a modern judicial system.